2017
DOI: 10.1016/j.socec.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Framing effects in intertemporal choice: A nudge experiment

Abstract: This paper experimentally investigates the framing effects of intertemporal choice using two different elicitation modes, termed classical and penal. In the classical mode, participants are given the choice between receiving a certain amount of money, smaller and sooner, today and a higher amount, larger and later, delayed (e.g., "€55 today vs. €75 in 61 days"). This is referred to as the standard mode. In the penalty mode, the participant must give up an explicit amount of money in order to choose the smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…Illegitimate tasks could decrease individuals’ self-control resources by creating cognitive load, triggering negative self-perceptions and negative emotions, which could lead them to a state of ego depletion and make it difficult for them to focus on work engagement, causing them to develop work disengagement. This was in line with existing research ( Faralla et al, 2017 ) which suggested that employees in a state of ego depletion were more sensitive to timely rewards and more likely to focus on short-term benefits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Illegitimate tasks could decrease individuals’ self-control resources by creating cognitive load, triggering negative self-perceptions and negative emotions, which could lead them to a state of ego depletion and make it difficult for them to focus on work engagement, causing them to develop work disengagement. This was in line with existing research ( Faralla et al, 2017 ) which suggested that employees in a state of ego depletion were more sensitive to timely rewards and more likely to focus on short-term benefits.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this research believed that when individuals consume their self-control resources in illegitimate tasks, they will not be able to focus on engaging in work behaviors either consciously or unconsciously, which will bring about the emergence of work disengagement. Furthermore, persons in a state of ego depletion are more sensitive to timely rewards and are more likely to focus on short-term benefits ( Faralla et al, 2017 ). This suggests that employees will keep a watchful eye on non-work behaviors that provide them with timely positive emotions or benefits than work behaviors that are characterized by “immediate input-delayed reward.” It has been found that individuals who are in ego depletion produce more behaviors against the rules and regulations ( Yam et al, 2014 ), less proactive behavior, and employees have lower task adaptability ( Deng et al, 2016 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The literature on the framing effect provides ample evidence suggesting that a simple alteration in one or a few words in the decision frame presented to subjects often leads to substantial behavioral changes observed from their actual choice. In the domain of intertemporal decision-making, several studies have documented the framing effect using comparable low-key interventions (Read et al 2005;Read, Frederick, and Scholten 2013;Fassbender et al 2014;Breuer and Soypak 2015;Faralla, Novarese, and Ardizzone 2017). Below are a few examples of such studies.…”
Section: The Manipulationmentioning
confidence: 99%
“…Some studies have also shown that ego depletion has a significant positive impact on workplace deviance (Christian and Ellis, 2011;Thau and Mitchell, 2010). In addition, subordinates in a state of ego depletion tend to show a low future-oriented style and are more sensitive to immediate returns (Faralla et al, 2017). Therefore, when the negative consequences of organizational deviance implemented by subordinates are in the future (negative evaluation of subordinates by organizations and supervisions), while the rewards are immediate (dissatisfaction is vented), such subordinates are likely to choose immediate satisfaction rather than consider the long-term impact of the future (Unger and Stahlberg, 2011).…”
Section: Theory and Hypothesesmentioning
confidence: 99%